Physical and respiratory therapy in the critically ill patient with obesity: a narrative review - Martínez-Camacho, Miguel Ángel; Jones-Baro, Robert Alexander; Gómez-González, Alberto; Morales-Hernández, Diego; Lugo-García, Dalia Sahian; Melo-Villalobos, Andrea; Navarrete-Rodríguez, Carlos Alberto; Delgado-Camacho, Josué (Frontiers in Medicine, 2024)
Obesity has become increasingly prevalent in the intensive care unit, presenting a significant challenge for healthcare systems and professionals, including rehabilitation teams. Caring for critically ill patients with obesity involves addressing complex issues. Despite the well-established and safe practice of early mobilization during critical illness, in rehabilitation matters, the diverse clinical disturbances and scenarios within the obese patient population necessitate a comprehensive understanding. This includes recognizing the importance of metabolic support, both non-invasive and invasive ventilatory support, and their weaning processes as essential prerequisites. Physiotherapists, working collaboratively with a multidisciplinary team, play a crucial role in ensuring proper assessment and functional rehabilitation in the critical care setting. This review aims to provide critical insights into the key management and rehabilitation principles for obese patients in the intensive care unit.